Analisis Kinerja Keuangan Pada PT. Adhi Karya (Persero)Tbk. Berdasarkan Keputusan Menteri BUMN No:100/MBU/2002 - Ningtyas, Muchlis Pamor; , Sri Murwanti, S.E., M.M (2016)
The purpose of this study was to determine the financial performance. Adhi Karya (Persero) Tbk for the period 2012-2015 is based on an assessment that refers to the Decree of the Minister for State Owned Enterprises No. KEP-100/ MBU / 2002. Based on the results of the study are expected to provide inputs or information for companies and investors to be used as consideration in an effort to improve or develop the financial performance in the future. Data collection techniques used is documentation, the documents in the form of periodic financial statements of the company in 2012-2015. Data were analyzed using techniques of evaluation by the Minister for State Owned Enterprises No. KEP-100 / MBU / 2002. As to analyze developments in financial performance. Adhi Karya (Persero) Tbk from 2012 to 2015 years using trend analysis techniques. Based on the results showed that financial performance. Adhi Karya (Persero) Tbk in 2012 awarded the Healthy category A, in 2013 awarded the Healthy category A and 2015 PT. Adhi Karya (Persero) Tbk get Healthy categories category A. Assessment of healthy or less healthy companies seen from the indicators that have been defined according to the Decree of the Minister for State Owned Enterprises No. KEP-100 /MBU/2002.